KISAH DAN MATERI DAKWAH NABI HUD - Sutrisno Sutrisno (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2017)
Prophets and messengers have the same role, that is, to bring the teachings of monotheism. However, their exposure of tawhid varies, adjusted to the level of thinking maturity of their people. Hud is a prophet and messenger sent to the people of ‘Ad. They lived in Al-Ahqaf (the Sandy Plains) and built countless buildings that had never been before. They had superior civilization and skills in such fields as agriculture, livestock breeding, and architecture. The arrival of Hud was not appreciated, but insulted and mocked. They are repeatedly reminded to return the Oneness of Allah and to abandon idolatry, but only a few of those who accept it. Finally, they were persecuted, and their civilization was destroyed. An archeologist did the research in 1990 and found the ruins believed to be the pillars of building that was formerly owned by the people of Aad 'and Iran. This story has been told in the Quran in several Surah, its substance and value are permanently maintained. However, its impression and lessons are different.